Optimal taper period in female swimmers based on blood lactate concentrations and performance - Kenitzer, R. F. (Medicine & Science in Sports & Exercise, 1998)
Female competitive swimmers (5 sprinters, 5 long-distance, 5 middle-distance) were studied during a four-week end of season taper. Training yardage was reduced by 25% weekly. Blood lactates and performances were evaluated after a 4 x 100 m test set. All groups were similar in performance and lactate values at the initial testing and so Ss were collapsed into a single group. The best values for performance and lactate were exhibited after two weeks indicating an effective taper. However, after that, signs of detraining occurred. Implication. In female swimmers, a taper of two weeks duration produces the best recovery.